Implikasi Larangan Ekspor Bauksit Oleh Pemerintah Indonesia Terhadap Kerjasama Indonesia Dan European Union Comprehensive Economic Partnership Agreement - Kurnia, Kana; Arfiani, Nur; Hadrian, Reza (Jurnal de jure, 2025)
The ban on bauxite exports shows the government’s consistency in encouraging downstream mining products, by processing bauxite domestically, added value can be enjoyed and has the potential to increase state revenue, but on the other hand there are international obligations that need to be followed by Indonesia related to the ban on exports of mining products. This article aims to analyze Indonesia's bauxite export ban policy according to international trade law and its impact on Indonesia - the European Union Comprehensive Economic Partnership Agreement (IEU-CEPA). To compile this article, normative research was conducted, where secondary data was obtained through literature examination. Then, a conceptual approach was used to conduct a qualitative descriptive analysis of literature sources relevant to the research subject. The results of this study indicate that Indonesia will most likely fail to prove that the bauxite export ban that has been implemented is justified according to the General Agreement on Tariffs and Trade 1994 (GATT 1994), one of the reasons is because the Indonesian government does not provide alternative policies related to the bauxite export ban and also the initial purpose of the bauxite export ban was because the government wanted to encourage domestic bauxite processing and refining, this is also evidenced by the absence of restrictions on domestic production and consumption, and also Indonesia must be prepared to face the latest lawsuits from the European Union or other countries considering that Indonesia is believed to have violated several articles in the GATT and the IEU-CEPA negotiations.